2013
DOI: 10.1056/nejmoa1206881
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Glucose Control with an Artificial Pancreas at a Diabetes Camp

Abstract: Patients at a diabetes camp who were treated with an artificial-pancreas system had less nocturnal hypoglycemia and tighter glucose control than when they were treated with a sensor-augmented insulin pump. (Funded by Sanofi and others; ClinicalTrials.gov number, NCT01238406.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
279
2
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 401 publications
(300 citation statements)
references
References 32 publications
9
279
2
7
Order By: Relevance
“…[40][41][42][43][44][45] The results from these investigations were summarized in a 2011 review of the artificial pancreas field, 46 pointing out the superiority of closed-loop control over insulin pump therapy in terms of (1) increased time within target glucose range, (2) reduced incidence of hypoglycemia, and (3) better overnight control. Subsequent studies confirmed these findings in outpatient setting, 47 at diabetes camps for children, 48 and at patients' homes. 49 The superior glucose control achieved by these trials suggests that when CGM information is processed appropriately by advanced algorithms, the clinical outcomes are better, even than those achieved by state-of-the art sensoraugmented insulin pump therapy.…”
Section: Utility Of Cgm Informationmentioning
confidence: 66%
“…[40][41][42][43][44][45] The results from these investigations were summarized in a 2011 review of the artificial pancreas field, 46 pointing out the superiority of closed-loop control over insulin pump therapy in terms of (1) increased time within target glucose range, (2) reduced incidence of hypoglycemia, and (3) better overnight control. Subsequent studies confirmed these findings in outpatient setting, 47 at diabetes camps for children, 48 and at patients' homes. 49 The superior glucose control achieved by these trials suggests that when CGM information is processed appropriately by advanced algorithms, the clinical outcomes are better, even than those achieved by state-of-the art sensoraugmented insulin pump therapy.…”
Section: Utility Of Cgm Informationmentioning
confidence: 66%
“…[12][13][14] This new study confirms the previous findings and adds two unique features: (1) a portable platform using a consumer electronics device (smartphone) to run the CLC system and all CGM, pump, and remote communications and (2) a control algorithm specifically designed to ''slide'' the patients' glucose levels to a target of 120 mg/dL at wakeup, thereby resetting their metabolic state overnight to near-normoglycemic morning BG levels, on consecutive nights. As a result, this study demonstrated not only significant improvement in overnight glucose control on CLC, but also significant improvement of patients' control on the next day.…”
Section: Discussionmentioning
confidence: 99%
“…9 The transition of CLC to a wearable outpatient system began in 2012 with the introduction of the Diabetes Assistant (DiAs)-the first wearable CLC system using a smartphone as a computational platform for its control algorithm. 10,11 Other recent trials confirmed the effectiveness of overnight CLC at diabetes camps for children 12 and at patients' homes, 13,14 placing laptop computers equipped with control algorithms at their patients' bedside.…”
mentioning
confidence: 90%
“…Closed-loop insulin delivery systems have recently been demonstrated to be safe and efficient in summer camps [11] and free-living conditions [12][13][14][15][16]. Data on closed-loop insulin delivery during physical activity is scarce [17,18], particularly in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%